Incidence of second primary cancers in patients with retinoblastoma: a systematic review and meta-analysis - Sun, Jinfeng; Gu, Xiuli; Wang, Liangjun (Frontiers in Oncology, 2024)
Introduction This systematic review and meta-analysis aimed to examine the risk of second primary cancers (SPCs) among retinoblastoma (Rb) patients, both hereditary and nonhereditary. Previous studies have reported on the long-term risk of SPCs in these patient populations, but a comprehensive synthesis of the existing evidence is lacking. Methods A systematic search was conducted in PubMed, EMBASE, and Cochrane Library from inception to 12 March 2023, supplemented by manual screening. Eligible studies were identified, and data were extracted. The primary outcome measure was the standardized incidence ratios (SIRs) of SPCs in Rb patients. Summary estimates were calculated using random or fixed effects models. The quality of included studies was assessed using the Newcastle-Ottawa Scale. Results Ten studies, including nine high-quality studies, were included in this review. The summary estimate of SIR for SPCs among hereditary Rb patients was 17.55 (95% CI=13.10-23.51), while the pooled estimate of SIR for SPCs among nonhereditary Rb patients was 1.36 (95% CI=0.90-2.04). Significant differences in SIRs for different SPC types were observed (P=0.028), including nasal cavity tumor (SIR=591.06, 95% CI=162.79-2146.01), bone tumor (SIR=442.91, 95% CI=191.63-1023.68), soft tissue sarcoma (SIR=202.93, 95% CI=114.10-360.93), CNS (SIR=12.84, 95% CI=8.80-18.74), and female breast cancer (SIR=3.68, 95% CI=2.52-5.37). Chemotherapy and radiation therapy were associated with an increased risk of SPCs among hereditary Rb patients. Discussion The findings of this review indicate that hereditary Rb patients have a significantly elevated risk of developing SPCs, whereas nonhereditary Rb patients do not show the same risk. Furthermore, significant differences were observed in the SIRs of different SPC types. Treatment techniques, specifically chemotherapy and radiation therapy, were associated with an increased risk of SPCs among hereditary Rb patients. These findings highlight the importance of radiation protection for Rb patients and the need for further research and tailored management strategies for this high-risk population.